The Empire in the Provinces: The Case of Carinthia - Konrad, Helmut (Religions, 2016)
This article examines the legacy of the Habsburg Monarchy in the First Austrian Republic, both in the capital, Vienna, and in the province of Carinthia. It concludes that Social Democracy, often cited as one of the six ingredients that held the old Empire together, took on distinct forms in the Republic's different federal states. The scholarly literature on the post-1918 heritage of the Monarchy therefore needs to move beyond monolithic generalizations and toward regionally focused comparative studies.